The Relevance between the Determination of Prison Penalties in Formulated Policies and the High Overcapacity in Correctional Institutions: Relevansi Antara Penetapan Pidana Penjara Dalam Kebijakan Formulasi Dengan Tingginya Kelebihan Kapasitas di Lembaga Pemasyarakatan - Khairil Ikhsan (Al-Mizan (e-Journal), 2022)
The policy of determining prison sentences contained in criminal law is one factor in the occurrence of excess capacity in the penitentiary in Indonesia. This research aims to analyze the concept of criminal policy, namely the application of imprisonment in criminal legislation. As normative legal research, this research uses a conceptual approach and legislation. The results of this study conclude that there is a relevance between the occurrence of excess capacity in the penitentiary and the formulation of existing policies in criminal law. The occurrence of overcapacity in prisons is inseparable from criminal law policies that use imprisonment as a threat to crime. The policy formulation for imposing prison sanctions contained in the majority law still adheres to cumulative sanctions, thereby limiting the choices of judges in imposing sentences. When the type of punishment chosen to be threatened with violating the norms of criminal law is imprisonment, it will have implications for increasing acts that are punishable by imprisonment which increases overcapacity in the penitentiary.